2017
DOI: 10.1093/gigascience/gix006
|View full text |Cite
|
Sign up to set email alerts
|

A reference gene set construction using RNA-seq of multiple tissues of Chinese giant salamander, Andrias davidianus

Abstract: BackgroundChinese giant salamander (CGS) is the largest extant amphibian species in the world. Owing to its evolutionary position and four peculiar phenomenon of life (longevity, starvation tolerance, regenerative ability, and hatch without sunshine), it is an invaluable model species for research. However, lack of genomic resources leads to fewer study progresses in these fields, due to its huge genome of ∼50 GB making it extremely difficult to be assembled.ResultsWe reported the sequenced transcriptome of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…We obtained higher total and mean data per specimen than reported in Anolis carolinensis, Lupinus angustifolius , or Pistacia vera. Due to the large genome of A. davidianus (~50Gb) analyzed by flow cytometry [30], the sequence coverage in this study averaged 0.29 x per salamander. The results were available to explore the sex-specific marker to identify the genetic sex of A. davidianus, especially the larvae and sex reversed individuals in the non-model species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained higher total and mean data per specimen than reported in Anolis carolinensis, Lupinus angustifolius , or Pistacia vera. Due to the large genome of A. davidianus (~50Gb) analyzed by flow cytometry [30], the sequence coverage in this study averaged 0.29 x per salamander. The results were available to explore the sex-specific marker to identify the genetic sex of A. davidianus, especially the larvae and sex reversed individuals in the non-model species.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the environmental degradation and human harvesting, the wild population has sharply decreased, and it is now classified as an endangered species. A.davidianus possesses 30 pairs of chromosomes with 19 pairs of microchromosomes [18] and a genome of ∼50 GB, making assembly a challenge [30]. Therefore, RAD-seq is a useful method to explore a sex-specific marker in A. davidianus .…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese giant salamander ( Andrias davidianus ) is a species that has been classified as a class II critically endangered species on the national list of protected animals in China. The Chinese giant salamander is often called a living fossil and is considered a valuable model species for phylogenetic and evolutionary studies (Geng et al ). Giant salamanders are susceptible to bacterial infections (Meng, Zeng, Yang, & Xiao, ).…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of our study was that just a single biological sample was used in the RNA‐seq. Also, it has been reported that the RNA‐seq was carried out only from a single biological sample in several researches (Geng et al, ; Liu et al, ; Gardner et al, ; Singh et al, ). In the present study, on the basis of RNA‐seq data, secondary and tertiary methods of analyses were used to validate the observed differences.…”
Section: Discussionmentioning
confidence: 99%